Spontanous Rupture of Urinary Bladder without Uterine Rupture (Journal of Medical Sciences, 2018)
Objective: Spontaneous bladder injury is very uncommon with incidence of about 1:126000. We report a case of intraperitoneal urinary bladder rupture with intact uterus, which diagnosed intraoperative of G2P1 with history of CS. The rent was repaired in layers, catheterization and antibiotic prophylaxis offered for 14 days. Cystogram was done before the removal of catheter.